Correction: Chlorine-doped SnO2 hydrophobic surfaces for large grain perovskite solar cells. Issue 33 (19th August 2020) - Gong, Wenxiao; Guo, Heng; Zhang, Haiyan; Yang, Jian; Chen, Haiyuan; Wang, Liping; Hao, Feng; Niu, Xiaobin
Abstract : Correction for 'Chlorine-doped SnO2 hydrophobic surfaces for large grain perovskite solar cells' by Wenxiao Gong et al., J. Mater. Chem. C, 2020, DOI: ; 10.1039/d0tc00515k .